2017
DOI: 10.1002/jbt.21977
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic effects of ellagic acid and rosmarinic acid on doxorubicin‐induced neurotoxicity in rats

Abstract: Doxorubicin (DOX) is a chemotherapeutic agent widely used in human malignancies. Its long-term use cause neurobiological side effects. The aim of the present study was to investigate the prophylactic effect exerted by daily administration of ellagic acid (EA) and rosmarinic acid (RA) on DOX-induced neurotoxicity in rats. Our data showed that DOX-induced significant elevation of brain malondialdehyde, tumor necrosis factor-alpha (TNF-α), inducible nitric oxide synthase (iNOS), caspase-3, and cholinesterase asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…RosA could effectively prevent DOX-induced neurotoxicity, and the underlying mechanism of neuroprotection was possibly related to its antioxidant, anti-inflammatory, and anti-apoptotic effects. (Rizk et al, 2017) Spinal cord injury RosA prevented the rise in the SCI-induced nuclear localization of NF-kB and the corresponding reduction in the nuclear localization of Nrf-2. RosA inhibited neuronal apoptosis through targeting ROS and inflammatory responses in SCI.…”
Section: Effect Of Rosmarinic Acid On Other Inflammatory Diseasesmentioning
confidence: 98%
“…RosA could effectively prevent DOX-induced neurotoxicity, and the underlying mechanism of neuroprotection was possibly related to its antioxidant, anti-inflammatory, and anti-apoptotic effects. (Rizk et al, 2017) Spinal cord injury RosA prevented the rise in the SCI-induced nuclear localization of NF-kB and the corresponding reduction in the nuclear localization of Nrf-2. RosA inhibited neuronal apoptosis through targeting ROS and inflammatory responses in SCI.…”
Section: Effect Of Rosmarinic Acid On Other Inflammatory Diseasesmentioning
confidence: 98%
“…Hydroxyl radicals and superoxide radicals along with hydrogen peroxide are produced after administration of DOX, leading to the alterations of oxidative stress and antioxidant defense system. It is assumed that the formation of free radicals induces oxidative stress and plays a crucial role in the mechanism of DOX-induced neurotoxicity [ 12 , 13 ]. Moreover, the generation of superoxide anions induced by DOX can elevate the level of circulating necrosis factor-alpha (TNF- α ) which can directly cross the blood-brain barrier and activate glial cells to initiate the local production of proinflammatory cytokines, exacerbating oxidative stress and neural apoptosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rizk et al demonstrated the prophylactic effects of EA (10 mg/kg/day, orally) on doxorubicin‐induced neurotoxicity in rats. They reported that EA strikingly attenuates the levels of MDA, TNF‐a, iNOS, caspase‐3, while increases the levels of GSH and monoamines namely serotonin, dopamine, and norepinephrine in the brain following doxorubicin‐induced neurotoxicity (Rizk, Masoud, & Maher, ). In another study, EA (17.5 and 35 mg/kg) improved the cognitive deficits and GSH content, while alleviated TBARS and TNF‐α levels in the brain of streptozotocin‐induced memory deficit rats (Bansal, Yadav, & Kumar, ).…”
Section: Resultsmentioning
confidence: 99%
“…Rizk et al demonstrated the prophylactic effects of EA (10 mg/kg/ day, orally) on doxorubicin-induced neurotoxicity in rats. They reported that EA strikingly attenuates the levels of MDA, TNF-a, iNOS, caspase-3, while increases the levels of GSH and monoamines namely serotonin, dopamine, and norepinephrine in the brain following doxorubicin-induced neurotoxicity (Rizk, Masoud, & Maher, 2017).…”
Section: In Vitro Studiesmentioning
confidence: 99%